2002
DOI: 10.1055/s-2002-25120
|View full text |Cite
|
Sign up to set email alerts
|

Selektive CT-Mesenterikographie zur Diagnostik schwerer Darmblutungen unklaren Ursprungs: Vorläufige Ergebnisse

Abstract: Preliminary results indicate that selective CTM is superior to MG in the evaluation of severe obscure overt intestinal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
1
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
2
4
1
5
Order By: Relevance
“…In concordance with the findings of Schürmann et al [19], we observed strong attenuation of the bowel wall on first phase scans (delay 15 seconds) rendering the detection of extravasated contrast material difficult. Second phase scans (delay 60 or 75 seconds) proved to be most suited to depict contrast material extravasated into the bowel lumen.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In concordance with the findings of Schürmann et al [19], we observed strong attenuation of the bowel wall on first phase scans (delay 15 seconds) rendering the detection of extravasated contrast material difficult. Second phase scans (delay 60 or 75 seconds) proved to be most suited to depict contrast material extravasated into the bowel lumen.…”
supporting
confidence: 92%
“…The source of obscure gastrointestinal bleeding is usually located in the small bowel [18] which is basically supplied with blood by the superior mesenteric artery. Hence, Schürmann et al introduced the technique of CT mesentericography with selective contrast material injection into the superior mesenteric artery [19]: following mesenteric DSA the catheter was left in the superior mesenteric artery, the patient was transferred to the CT suite and the entire abdomen was scanned after contrast material injection via the catheter. The rationale of CT mesentericography is to obtain an extremely high contrast material concentration within the superior mesenteric artery in order to identify contrast material extravasation into the bowel lumen even when faint bleeding is present.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Falls diese dennoch unklar bleibt, ist der Einsatz angiographischer Techniken, gegebenenfalls in Kombination mit der Computertomographie, indiziert. Hierbei kann gleichzeitig durch selektive Okklusion des blutenden Gefäßes mit unterschiedlichen Agenzien eine Blutstillung herbeigeführt werden [90][91][92][93][94][95]. Als letzte Möglichkeit zur Lokalisation einer Blutungsquelle verbleibt die Szintigraphie, die jedoch allein diagnostischen Charakter hat und der in der Regel operativen Schritte folgen müssen.…”
Section: Diagnostik Und Managementunclassified
“…Eine besondere Variante ist die selektive CT-Mesenterikographie, bei der der Patient mit in der A. mesenterica superior liegendem Katheter ins CT gebracht wird und dort nach einem selektiven Kontrastmittelbolus mit einer schnellen Bildfolge dünner Schichten untersucht wird. In einer kleinen Pilotstudie mit lediglich 8 Patienten konnte dabei die Überlegen-heit dieser Technik gegenüber der konventionellen DSA gezeigt werden (16). Im Fall einer transpapillären Blutung wie bei Haemosuccus pancreaticus muss darauf geachtet werden, dass neben der A. mesenterica superior und ihren Ästen auch die lienalen Äste und Kommunikationen über den Truncus coeliacus mit dargestellt werden.…”
Section: Schwer Diagnostizierbare Blutungsquellenunclassified